2021
DOI: 10.3390/cancers13061235
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Signaling Pathways and Proteasome Inhibitors Combinations in Multiple Myeloma

Abstract: Multiple myeloma is a malignancy of terminally differentiated plasma cells, characterized by an extreme genetic heterogeneity that poses great challenges for its successful treatment. Due to antibody overproduction, MM cells depend on the precise regulation of the protein degradation systems. Despite the success of PIs in MM treatment, resistance and adverse toxic effects such as peripheral neuropathy and cardiotoxicity could arise. To this end, the use of rational combinatorial treatments might allow lowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 234 publications
(317 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, anti-mitochondrial agents have shown to restore the sensitivity of myeloma cells to proteasome inhibitors [ 39 ]. The combination of metabolic regulators with proteasome inhibitors may induce synthetic lethality, prevent the activation of resistance mechanisms and increase efficacy [ 141 , 149 ]. Recently, preclinical studies have shown that adaptive natural killer cells have decreased CD38 expression and enhanced metabolic fitness by resisting oxidative stress, which may lead to improved anti-myeloma activity in the relapsed disease setting [ 150 , 151 ].…”
Section: Myeloma Treatment and Metabolismmentioning
confidence: 99%
“…Interestingly, anti-mitochondrial agents have shown to restore the sensitivity of myeloma cells to proteasome inhibitors [ 39 ]. The combination of metabolic regulators with proteasome inhibitors may induce synthetic lethality, prevent the activation of resistance mechanisms and increase efficacy [ 141 , 149 ]. Recently, preclinical studies have shown that adaptive natural killer cells have decreased CD38 expression and enhanced metabolic fitness by resisting oxidative stress, which may lead to improved anti-myeloma activity in the relapsed disease setting [ 150 , 151 ].…”
Section: Myeloma Treatment and Metabolismmentioning
confidence: 99%
“…To overcome the cardiotoxicity of PIs like carfilzomib, mitochondrial functions affected by PIs are being dissected, and novel PIs devoid of cardiotoxicity are also being developed and analyzed in preclinical studies [222]. Combination strategies reducing PI doses are currently being evaluated in clinical trials to counteract dose-dependent CVAEs [223].…”
Section: Proteasome Inhibitors (Pis)mentioning
confidence: 99%
“…This problem becomes even more important nowadays because new drugs for MM treatment appear every year. Some of these drugs are based on new principles of action (e.g., monoclonal antibodies, CAR T-cell therapy, targeted delivery of chemotherapeutic drugs, such as melphalan flufenamide or antibody–drug conjugates), while others are developed on a platform of new knowledge about the genetic plasticity of the MM genome (e.g., histone deacetylase inhibitors, drugs targeting DNA or histone’s methylation pathways, pyrimidine nucleoside analogs) [ 103 , 130 , 132 , 719 , 720 , 721 ]. Next-generation IMiDs, PIs, agents that target the ubiquitin proteasomal cascade, and signaling pathways, are being developed to overcome the limitations of existing therapies [ 719 , 722 , 723 ].…”
Section: Conclusion and Further Perspectivesmentioning
confidence: 99%